STRUCTURAL DESIGN OF DECK ON PILE DRY BULK JETTY STRUCTURE IN PLTU SURALAYA, PULOMERAK DISTRICT, CILEGON CITY, BANTEN - Iqbal Al-Fathan, Moh
Indonesia is one of the largest archipelagic countries in the world, with such geography it is necessary to improve various facilities in an effort to fulfill the needs of the community so that well-being can be more evenly distributed throughout the country. One of the basic needs of the community is the need for electrical energy, one form of fulfillment is by building a Steam Power Plant (PLTU) with the main fuel, which is coal, one of the large PLTUs that distributes electrical energy to several areas of West Java and DKI Jakarta is PLTU Suralaya, which over time is getting bigger and requires its own dock facilities to supply coal more effectively. This Final Project discusses the design of a dry bulk jetty structure at the Suralaya Steam Power Plant, Pulomerak District, Cilegon City, Banten which contains the design of a jetty structure with the aim of serving coal unloading. The scope of discussion of the Final Project includes data collection and processing, preliminary design of the structure to withstand the working load, modeling and analysis of the structure with SAP 2000 software, design of structural element reinforcement, along with bearing capacity analysis of the soil structure. Structural elements in the design include beams, plates, piles, and pile caps. Modeling and analysis of the structure will be carried out in accordance with the limits of UCR values and deflections that are acceptable to the structure according to standard limits. The output of the modeling is in the form of an optimum design and the internal forces and reactions of the jetty structure will be obtained which will be used in the design of structural element reinforcement and soil bearing capacity analysis. The designed jetty structure has dimensions of 260 m long and 30 m wide with an elevation of +3.5 m from LWS. Based on the optimum structural design, the piles used for the structure are 1000 mm with a thickness of 20 which need to be driven to a depth of 25 m below the seabed in order to meet the axial and lateral force requirements. The results of this Final Project are the dimensions of the structure along with the dimensions of the structural elements of the structure, berthing and mooring facilities, details of the reinforcement of the structural elements of the pier, along with the depth of pile driving needed.